2018
DOI: 10.1093/jisesa/iey065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Diversity, Vegetation Composition, and Habitat Type on Different Functional Trait Groups of Wild Bees in Rural Beijing

Abstract: The loss of flower-rich habitats and agricultural intensification have resulted in significant losses of wild bee diversity from agricultural landscapes that is increasingly threatening the pollination of zoochorous agricultural crops and agricultural sustainability. However, the links of different wild bee functional trait groups with habitat types and plant resources in agricultural landscapes remain poorly understood, thus impeding the formulation of effective policies for bee conservation. We therefore ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(76 reference statements)
1
7
0
1
Order By: Relevance
“…Our findings show that the community of bees also responds positively to the structure of vegetation, corroborating recent studies (e.g. Wu et al, 2018;Alvarenga et al, 2020). As expected, we found a positive effect of tree species richness on the abundance and species richness of bees.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings show that the community of bees also responds positively to the structure of vegetation, corroborating recent studies (e.g. Wu et al, 2018;Alvarenga et al, 2020). As expected, we found a positive effect of tree species richness on the abundance and species richness of bees.…”
Section: Discussionsupporting
confidence: 93%
“…Another factor that can affect the distribution of bees is the structure of vegetation (Wu et al, 2018). There is evidence that the richness and abundance of bees is positively related to the richness of plants and the abundance of potential nesting resources (Grundel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest forager abundance and colony weight was shown in agricultural areas, which indicated that agricultural areas had a negative effect on bees. Research by [26] showed that bee species have distinct preferences for different plant communities, and their abundance is related to the abundance of their host plants. Agricultural areas that are dominated by certain crop plants might affect the fitness and population growth of bees.…”
Section: Discussionmentioning
confidence: 99%